Crossing Borders, (Re)Shaping Gender. Music and Gender in a Globalised World - Luis Lemos (e-cadernos ces, 2011)
Music is known to be one of the most visible forms of artistic expression through which traditional patriarchal values in society can be contested and challenged. However, it has not been recognised to what extent globalisation has enhanced or hindered the use of music as a tool for gender equality. Therefore, it is necessary to find linkages between gender and music in globalisation processes. Based on case studies, this paper will illustrate how music has changed or perpetuated traditional social relations within societies and how this was only possible due to an increasing exchange of cultural, economic and social values, and ideas.